Homodimerisation of the lymph vessel endothelial receptor LYVE-1 through a redox-labile disulfide is critical for hyaluronan binding in lymphatic endothelium - Banerji, S; Lawrance, W; Metcalfe, C; Briggs, D; Yamauchi, A; Dushek, O; Van der Merwe, P; Day, A; Jackson, D (American Society for Biochemistry and Molecular Biology, 2016)
The lymphatic vessel endothelial receptor LYVE-1 is implicated in uptake of hyaluronan (HA) and trafficking of leucocytes to draining lymph nodes. Yet LYVE-1 has only weak affinity for hyaluronan, and depends on receptor clustering and higher-order ligand organisation for durable binding in lymphatic endothelium. An unusual feature of LYVE-1 not found in other HA receptors is the potential to form disulfide-linked homodimers. However their influence on function has not been investigated. Here we show LYVE-1 homodimers are the predominant configuration in lymphatic endothelium in vitro and in vivo and formation requires solely the unpaired cysteine residue C201 within the membrane-proximal domain, yielding a 15 fold higher HA binding affinity and ~ 70 fold slower off-rate than monomer. Moreover, we show non-dimerising LYVE-1 mutants fail to bind HA even when expressed at high densities in lymphatic endothelial cells or artificially crosslinked with antibody. Consistent with these findings, small angle X-ray scattering (SAXS) indicates the C201 interchain disulfide forms a hinge that maintains the homodimer in an open scissors conformation, likely allowing arrangement of the two HA binding domains for mutual engagement with ligand. Finally, we demonstrate the C201 interchain disulfide is highly labile and selective reduction with TCEP-HCl disrupts LYVE-1 honodimers, ablating HA binding. These findings reveal binding is dependent not just on clustering but also on the biochemical properties of LYVE-1 homodimers. They also mark LYVE-1 as the first Link protein superfamily member requiring covalent homodimerization for function and suggest the interchain disulfide acts as a redox switch in vivo.